Knowledge Level Relationship with Smoking Behavior in Senior High School (SMA) Students in the Region - Wicaksono, Rizky Rahadian; Hilal, Achmad; Asmah, Nur (International Journal of Health Sciences, 2025)
Smoking is one of the risky behaviors that often begins in adolescence. Although information about the dangers of smoking is increasingly widespread, smoking behavior is still a fairly high phenomenon among students, including high school students. This study aims to determine the relationship between the level of knowledge about the dangers of smoking and smoking behavior among high school students in an area. The research method used is quantitative with a cross-sectional approaches . The sample in this study amounted to 150 students from three high schools selected purposively. Data were collected through questionnaires that have been tested for validity and reliability. The results showed that most students had a good level of knowledge (58%), but smoking behavior was still quite high (40%). Statistical tests showed a significant relationship between the level of knowledge and smoking behavior (p <0.05). It can be concluded that good knowledge does not always guarantee healthy behavior if it is not supported by other factors such as the environment, peers, and parental supervision. A comprehensive approach is needed through ongoing health education and the involvement of all parties to reduce the number of smokers among adolescents.